ANALISIS PENGARUH PELATIHAN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA BIDAN YANG BERDAMPAK PADA KEPUASAN KERJA DI KABUPATEN BANGKA BARAT - Eva Farida; Hamdan Hamdan (JEM Jurnal Ekonomi dan Manajemen, 2019)
To achieve and realize the goals of an organization both private and public organizations must be based on good and structured planning and supported by reliable and skilled human resources so that it is more efficient and effective in achieving goals. This study aims to determine and analyze the effect of training, motivation, and work environment on the performance of midwives in West Bangka Regency. This study used a sample of 154 midwives in West Bangka Regency as respondents. With the method of taking Probability Sampling. This study concludes that there is an effect of training, motivation and work environment on the performance of midwives in West Bangka Regency.